Ijaz dan Ithnab sebagai Bentuk Retorika Bahasa al-Qur’an - Fatimah Zahrah; Nabila Umayrah (ALSYS, 2026)
The Qur’an has distinctive linguistic and rhetorical characteristics through the use of ijaz and ithnab as techniques for conveying divine messages. Ijaz is a rhetorical style that conveys broad and profound meaning through concise and compact expressions, whereas ithnab is an expanded form of expression used to clarify, emphasize, and strengthen meaning. This study aims to examine the definition, types, and rhetorical functions of ijaz and ithnab in the Qur’an as part of balaghah studies. This study used a textual analysis method with linguistic and rhetorical approaches focusing on language structure, diction, and style in Qur’anic verses. The results showed that ijaz played an important role in conveying theological concepts and spiritual values concisely yet comprehensively, whereas ithnab functioned to elaborate and emphasize meaning through the deliberate expansion of expression. These two techniques complement each other in constructing the richness of meaning, linguistic beauty, and depth of the Qur’anic message. The conclusion of this study emphasizes that ijaz and ithnab represent the miraculous nature of the Qur’an from linguistic and rhetorical perspectives. The implications of this study provide a contribution to strengthening balaghah studies and understanding the rhetorical strategies of the Qur’an in conveying theological and spiritual messages.